Pengenalan dan Sosialisasi Potensi Hotspring Oi Pana di Hu’u, Kabupaten Dompu Sebagai Manifestasi Geologi Permukaan - Putra, ZA Munarfan; Faesal, Andi; Ubaidillah, Aji Syailendra; Erintina, Melinda Dwi; Felisa, Maritsha Safa (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2026)
Hu’u hot spring is a natural resource that emerges as a surface geological manifestation related to subsurface geothermal activity and has scientific and educational value for the local community. However, local community understanding of the geological processes, characteristics, and potential utilization of the hot spring remains limited, resulting in underutilization that is not yet knowledge-based or sustainable. This community service program aimed to introduce the potential of the Hu’u hot spring as a surface geological manifestation and to improve community awareness and understanding of its geological significance. The program was conducted using an educative and participatory approach, consisting of preparation, socialization and education, limited field observation, and qualitative evaluation. Educational activities were delivered through counseling sessions, interactive discussions, and simple visual media to explain basic geological concepts related to hot spring formation, while field observations were conducted directly at the hot spring site to identify observable surface manifestations. The results showed a measurable improvement in community understanding, indicated by increased participant ability to explain the origin of the hot spring, recognize key surface geological features, and articulate the importance of environmental preservation around the site. Participant engagement during discussions increased significantly, with more than two-thirds of attendees actively participating in question-and-answer sessions. The program also resulted in increased community awareness regarding the sustainable use of the hot spring as a local natural resource. Overall, this community service activity successfully enhanced geoscience literacy and provided a foundation for future community-based and sustainable utilization of the Hu’u hot spring.